β-Lactones Inhibit N-acylethanolamine Acid Amidase by S-Acylation of the Catalytic N-Terminal Cysteine - Armirotti, Andrea (American Chemical Society, 2012)
[Image: see text] The cysteine amidase N-acylethanolamine acid amidase (NAAA) is a member of the N-terminal nucleophile class of enzymes and a potential target for anti-inflammatory drugs. We investigated the mechanism of inhibition of human NAAA by substituted β-lactones. We characterized pharmacologically a representative member of this class, ARN077, and showed, using high-resolution liquid chromatography–tandem mass spectrometry, that this compound forms a thioester bond with the N-terminal catalytic cysteine in human NAAA.